Domínios ferroelétricos em cerâmicas e materiais nanoestruturados: investigação por microscopia de piezoresposta - Bastos, Wagner Benício (2011)
In this work, ferroelectric domain structure was investigated by Piezoresponse Force Microscopy (PFM). To this, an Atomic Force Microscope (AFM) has been modified to use it as PFM at room temperature and at high temperatures. Ferroelectric ceramics were used in the as bulk ceramic samples of Pb(Zr0,40Ti0,60)O3 (PZT 40/60) and (Pb0,79La0,21)TiO3 (PLT 21) produced by conventional methods. Nanostructured materials of Pb(Zr0,40Ti0,60)O3 (PZT 40/60) and Pb(Zr0,20Ti0,80)O3 (PZT 20/80) prepared respectively by sputtering and oxide precursors method were also studied. In a bulk ceramic PZT 40/60 was observed patterns of ferroelectric domain in twins configuration and built a three-dimensional model of its structure. The behavior of the polarization through the domain walls of 90o and 180o was investigated and widths of domains walls were estimated to be about 29 nm and 75 nm, respectively. In nanostructured samples PZT 40/60 and PZT 20/80, piezoelectric hysteresis remaining cycles, obtained by local measurements on different grains, shown a strong influence between the crystallographic orientation and the remanent polarization in each grain. Studies of polarization reorienting performed by ferroelectric lithography PFM revealed that the vertical component of the polarized material depends only on the vertical direction of the applied electric field, while the component parallel to the surface of the sample depends on the movement of the tip on its surface. This allows a procedure to control the orientation of these two components in the material. It was accompanied by images of PFM developments ferroelectric domains of ceramic PLT 21 (TC ~ 125oC) at high temperatures. The surface of the sample showed ferroelectric characteristics even at temperatures of 142°C. The results showed that the intensity of the polarization in the regions with a domain pattern decreases with increasing temperature.